Relationship between somatic build and kinematic indices of underwater undulatory swimming performed by young male swimmers - Wadrzyk, L.; Staszkiewicz, R.; Zeglen, M.; Kryst, L. (International Journal of Performance Analysis in Sport, 2021)
The study aim was establishing relationships between somatic build and kinematic indices describing underwater undulatory swimming (UUS). In a group of 47 young male swimmers (age = 17.2 ± 1.01, FINA points per 100 freestyle = 553 ± 94), anthropometric measurements were conducted. UUS was recorded through an underwater window. Movement modelling and its kinematic analysis were conducted using the SkillSpector. Velocity (vCOM), frequency (f), movement amplitude (A), distance per cycle (DPC) and product (IAf) were determined. Anthropometric variable reduction was performed using principal component analysis (PCA). Then, a correlation matrix was created containing distinguished components and kinematic variables (p < 0.05). Intra-group variance was explained by 9 components (i.e. 90%), concerning indices of body size, adiposity and limb proportions. Few, weak relationships between principle components and kinematic indicators of UUS were proven. However, no component was found as related to vCOM. Simultaneously, all kinematic variables (f, A, DPC, IAf) had influence on velocity, creating medium to strong correlations. Influence of swimmers` somatic structure on UUS efficacy was small. Correct UUS technique was the main factor influencing effectiveness regarding the tested manner of movement. Therefore, an inseparable element of training young swimmers should be UUS technique exercises.